PERJANJIAN KERJASAMA MENGENAI PENYEDIAAN TANAH DAN PEMBANGUNAN RUMAH DI ATASNYA - , LISSA DIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The author chose the title Final Report "Cooperation Agreement Concerning the Provision of Land and Housing Developmenton it." Because according to the author of the interesting cases, usually if there is an agreement of the parties do no deed made or was authorized before Notary to get legal power over the agreement made the parties. Made before a Notary Deed is perfect evidence. The purpose of the implementation of the Job Practice to meet the graduation requirements of the Diploma Program 3 Vocational School of Law, Gadjah Mada University and earned his Associate Expert for Law, in addition to giving a real experience to the author as an expert in the field of labor law, to apply the theory and knowledge that has been acquired during the lectures with the world of work, to get to know and understand about the Notary and PPAT, to know and understand about a treaty is one of the co-operation agreement and know the procedures in the partnership agreement deed. Field Work Practice activities is of great benefit to the author, because in spite of all the theories that the author can in college often there are differences in practices that occur in the field. An agreement is an event in which a promise to another person or in which the person is mutually pledge to implement something. From that event, occur a relationship between two people that are in the call of the engagement, the relationship between engagement and agreement is that it publishes engagement agreement, then the agreement is the source of the engagement. Cooperation is an effort between individuals or groups of people in both parties for a common goal to get results faster and better. Cooperation is intended as a business / work or joint venture between individuals or groups of people to achieve one or more goals.